Choosing the Right Blackberry Cultivar in Subtropical Florida - Shinsuke Agehara; Syuan-You Lin; Zhanao Deng (EDIS)
Blackberry (Rubus spp.) is a deciduous berry crop and the fourth most economically important berry crop in the United States. Driven by the growing demand for blackberries, production recently expanded to the southeastern United States. In Florida, however, commercial blackberry production is limited primarily to small commercial U-pick operations. The main challenges include insufficient chill hours and poor fruit quality associated with the subtropical climate. This new 6-page article, a publication of the UF/IFAS Horticultural Sciences Department, will discuss important cultivar selection criteria and recommended blackberry cultivars in subtropical Florida. Written by Shinsuke Agehara, Syuan-You Lin, and Zhanao Deng. https://edis.ifas.ufl.edu/hs1352